PERCEIVED FACTORS INFLUENCING INTERNATIONAL INVESTMENT IN MALAYSIA - Yusufua , Abel Anafi; Apparavu, Kantharow; Singh , Jugindar Singh Katar (Electronic Journal of Business and Management, 2022)
This study investigates the perceived factors that influence the inflow of foreign direct investment (FDI) into Malaysia. A survey method was used to collect data from 210 employees of MNCs operating in Malaysia, primarily targeting foreign employees in managerial positions. Questionnaires were distributed both electronically and by hand. The analysis was conducted using SPSS, utilizing Pearson correlation and multiple regression analysis to assess the relationship between the determinants (market size, infrastructure development, resources, and social factors) and FDI inflows. The results suggest that only resources significantly contribute towards FDI inflow into Malaysia. In contrast, social factors, infrastructure, and market size failed to significantly influence FDI. These findings provide a pathway for foreign policy development to improve specific industries within Malaysia.